"It Was My Understanding That There Would Be No Math": Using Thematic Cases to Teach Undergraduate Research Methods. Issue 2 (3rd April 2018) - Oldmixon, Elizabeth A.
ABSTRACT: Undergraduates frequently approach research methods classes with trepidation and skepticism, owing in part to math-phobia and confusion over how methodology is relevant to their interests. These self-defeating barriers to learning undermine the efficacy of methods classes. This essay discusses a strategy for overcoming these barriers—use of a case study as a thematic framework for the class. In theory, the case study engages students and renders the material less abstract. A research methods class recently taught by the author was organized around political assassinations, with an initial framing focus the assassination of President John F. Kennedy. In an end of semester Qualtrics survey, students reported that they liked this approach and believe that it kept them interested in the material."[S]tats are dry. The Kennedys are not dry." ∼A student